Communicative Language Teaching: Exploring Theoretical Foundations and Practical Challenges - Kustiwan Syarief (Universitas Negeri Malang, 2016)
The genesis of Communicative Language Teaching (CLT) can be traced back to the 1970s when researchers and language practitioners began reflecting and discussing the notion of communicative competence. In practical terms, however, there has been such a gap between theoretical foundations of CLT on the one hand and its implementation in classroom environments on the other hand. This article explores and discusses the theoretical foundations of CLT based on the existing models of communicative competence and continues with identifying CLT's practical challenges commonly persisting in second/foreign language teaching and learning contexts.